The effect of simultaneous training and magnesium lactate on lactic endurance and complex offensive skills for under-19 football players (Damu Journal of Sport Sciences, 2025)
The research aims to identify the effect of simultaneous training and magnesium lactate on lactic endurance and complex offensive skills for under-19 football players.The researcher adopted the experimental method with the design of two equivalent experimental groups with a pre- and post-test as a basis for implementation, due to its suitability to the nature of the research problem.The researcher deliberately identified the research community as football players represented by Karbala Sports Club, aged under (19 years), numbering (23) players for the training season (2023-2024). The research sample was selected at (14) players. The training included (24) training units, and the training took (8) weeks to implement, at (3) training units per week. Each training unit included (4) exercises. The researcher used the training method of simultaneous training, which stipulates giving successive training in the same training unit between aerobic and anaerobic training. The researchers concluded: The effect of magnesium lactate has a great impact in preventing cramps and injuries due to the high muscle tone that occurs to players, as it is a recovery supplement. Simultaneous training has a positive effect on developing complex offensive skills.